Manuscritos Journal: New Forms of Resistance During the Chilean Dictatorship; [Revista Manuscritos: Nuevas Formas de Resistencia Durante la Dictadura Chilena] - Zamorano-Diaz, C (University Library System, University of Pittsburgh, 2019)
This work proposes to understand the political and cultural coordinates in which the appearance of the only number of the journal Manuscritos inscribes. Articulated in a space beleaguered by the military repression, Manuscritos channels forms of artistic production along with a writing that resignifies it. Thereby, the novelty of its written-visual construction is framed in the interior of a tradition through an affiliation with a past, working as an updated device of resistance, by recoding the space and time, which in the context of dictatorial (tabula rasa) are taken as unsettling and subversive. © 2019 The Author(s).
Keywords: Manuscritos Journal; Quebrantahuesos; Ronal Kay; Chilean Dictatorship